An atypical presentation of pediatric malignant spinal cord compression - Gaia, Maria João; Lopes, Vilma; Tenente, Joana; Coelho, Janine; Vila Real, Marta; Santos, Fátima (BIRTH AND GROWTH MEDICAL JOURNAL, 2024)
Background: Malignant spinal cord compression (MSCC) is a rare but serious complication of pediatric malignancies that can result in permanent neurologic deficits. The prognosis depends on neurological symptoms at diagnosis. Case report: A nine-year-old girl was evaluated for worsening pain in the left anterior iliac spine with one month of evolution. Over the next two days, she showed progressive gait instability and low back pain. During hospitalization, she developed decreased strength and sensitivity in the lower limbs, hyperreflexia with clonus, Babinski sign, and inability to walk. Magnetic resonance imaging showed a compressive intracanalicular lesion at D8-12, later identified as Ewing sarcoma. The patient was treated and had no sequelae. Conclusion: Clinicians should be aware that MSCC may have an atypical presentation, such as pain in an unusual location, and early recognition is essential to improve prognosis.